2013
DOI: 10.3899/jrheum.120400
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Nonbiologic versus Biologic Disease-modifying Antirheumatic Drugs for Rheumatoid Arthritis

Abstract: Patients in both treatment groups generally experienced lower CDAI scores across time. Patients switching to bDMARD demonstrated greater improvement than patients switching to nonbiologic DMARD with both analytic approaches at 5 months. Relative advantages with bDMARD were observed at 9 and 24 months only with MV regression. These analyses provide a practical example of how findings in comparative effectiveness research can diverge with different methodological approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Propensity scoring also reduces the statistical power of an analysis, as shown in a Corrona study comparing csDMARDs and biologics. 29 Also, we used the inverse probability treatment weighting method to create weights based on the propensity score. Since we did not use propensity score matching to create two comparable monotherapy and combination therapy groups, we cannot provide a comparison of matched monotherapy vs combination therapy cohorts in order to evaluate how well other covariates are balanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propensity scoring also reduces the statistical power of an analysis, as shown in a Corrona study comparing csDMARDs and biologics. 29 Also, we used the inverse probability treatment weighting method to create weights based on the propensity score. Since we did not use propensity score matching to create two comparable monotherapy and combination therapy groups, we cannot provide a comparison of matched monotherapy vs combination therapy cohorts in order to evaluate how well other covariates are balanced.…”
Section: Discussionmentioning
confidence: 99%
“…To control for channelling bias, all patients receiving monotherapy or combination therapy were matched using a propensity score matching method. 28 29 The propensity score was estimated using CDAI and patient sex. These variables were chosen following an analysis of the data using other possible risk factors (swollen and tender joint counts, CDAI, physician global assessment of disease activity, history of csDMARD use and history of MTX use).…”
Section: Methodsmentioning
confidence: 99%
“…Registry study data can be used to examine whether longer-term exposure to a biologic maintains the benefits for reduced disease activity and function impairment. Previous analyses of registry data have shown that RA patients who respond to biologic therapy in the first 6-12 months usually experience persistent benefits if they continue biologic therapy for several years [15][16][17][18][19][20][21][22][23][24]. The objective of this analysis was to examine the effect of cumulative exposure to biologics on patient outcomes over time, as well as predictors for improvement in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…compared the biological and nonbiological drugs in RA patients and found that biological drugs combined with Methotrexate exerted an effect similar to nonbiological drugs used as triple therapy. [9] Another study carried out in the Netherlands compared the effect of biological drugs and DMARDs on RA patients for 2 years. The results indicated that recovery was faster in the group that received biological drugs plus Methotrexate.…”
Section: Discussionmentioning
confidence: 99%